A clínica da adolescência numa perspectiva winnicottiana: especificidades, acompanhamento com os pais e possibilidades terapêuticas - Bichuetti, Luciana Pontes (2018)
Nowadays, the transformations resulting from globalization, from technological advances and from the new conditions of being and living have generated numerous difficulties that worsen every day, leading to a worrying increase in psychopathologies affecting adolescents worldwide. We have witnessed a significant increase in the demand for psychological care in public and private health services. Given this scenario, this work aimed to investigate, through Winnicott clinical cases and vignettes of my professional practice, the specificities, the possible dialogues with the parents and the therapeutic possibilities of the clinic with adolescents, from a Winnicottian perspective. To this end, a study was made of the emergence of the notion of adolescence, as we conceive it today and of the maturational process characteristic of this phase, from the Freudian postulates to the formulation of contemporary psychoanalysts, with special emphasis on Winnicottian theory, for contemplating these aspects more comprehensively. It was evidenced that the psychoanalytic process can offer subsidies to help adolescents in their difficulties and contribute to maturity at this stage. The professional who has the purpose of providing care for adolescents needs to prepare for this type of work. The winnicottian clinic has as main specificities the need to know the process of maturation, because the disturbances are understood as paralyzes in the course of this process; the expansion of the analytical setting, to include the family, the school, among others; the use of management; the provision of a facilitating environment for maturation; besides the care of the analyst with his own maturity. Follow-up with parents is valued and carried out wherever possible because they are understood as enabling environments for maturation for their children. The therapeutic possibilities vary according to the needs and possibilities of each case, being related to the resumption of developments that were interrupted and the propitiation of the maturation inherent to that phase. Because it is qualitative research, these data can not be generalized, however, it has been shown that the possibility of helping young people in this phase can contribute so that they can develop their true self to live creatively and feel that their life is full of meanings